An analysis of gains to acquiring firm's shareholders - Allen, Paul R.; Sirmans, C.F. (Journal of Financial Economics, 1987)
This study uses capital market data to measure the effects of REIT mergers on the wealth of the acquiring trust's shareholders. A significant increase in shareholder wealth is detected. This differs from the findings of other acquisition studies. The primary source of the value gain seems to be improved management of the acquired trust's assets.